Instrumentation for SCC testing in low pressure superheated hydrogen steam environments. (December 2018) - Janoušek, J; Scenini, F; Volpe, A; Hojná, A; Trojan, T
Abstract : This contribution is focused on the issue of Environmentally Assisted Cracking (EAC). For EAC testing in low pressure superheated hydrogen steam environments a special corrosion apparatus is being built in cooperation with University of Manchester and Škoda JS. The whole concept is being prepared for the MEACTOS project. One section concerns the problems with determining an environment with a mixture of hydrogen, argon and steam. The presented equations are necessary for controlling the environment and for the settings of the area of test interest. The test instrumentation is described.